1984
DOI: 10.2172/6918331
|View full text |Cite
|
Sign up to set email alerts
|

Environmental monitoring at the Lawrence Livermore National Laboratory. 1983 annual report

Abstract: NOTICE has been «P™^ broa dest possible »«><• Distribution Category UC-11 ability. DISCLAIMER This report was prepared as an account of work sponsored by an agency of the United States Government. Neither the United States Government nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes a»iy legal lir ility or responsi bility for the accuracy, completeness, or usefulness of any information, appc 'us, product, or process disclosed, or represents that its use woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Ura nium measurements were made by gamma spec trometry. As in the past, the analyses indicated that perturbation is essentially limited to areas adjacent to the firing bunkers (Griggs and Buddemeier, 1986;Gudiksen et al, 1973). With the exception of variations in the elevated 238 U concentrations near the bunkers, there were negligible changes from activities observed in previous samples collected in the same locations.…”
Section: Soil Monitoringmentioning
confidence: 70%
See 1 more Smart Citation
“…Ura nium measurements were made by gamma spec trometry. As in the past, the analyses indicated that perturbation is essentially limited to areas adjacent to the firing bunkers (Griggs and Buddemeier, 1986;Gudiksen et al, 1973). With the exception of variations in the elevated 238 U concentrations near the bunkers, there were negligible changes from activities observed in previous samples collected in the same locations.…”
Section: Soil Monitoringmentioning
confidence: 70%
“…The 1985 Environmental Monitoring Annual Report (Griggs and Buddemeier, 1986) briefly summarized the soil and groundwater investiga tive work performed during the period from the early 1980s through 1985. The schedule of tasks in CRWQCB, San Francisco Bay Region, Waste Dis charge Order No.…”
Section: Llnl Ground Water Projectmentioning
confidence: 99%
“…All data analyzed in this paper have been reported in LLNL site annual environmental reports (Silver et al 1977, 1978, 1979, 1980Toy et al 1981;Auyong et al 1982;Griggs et al 1983Griggs et al , 1984Griggs et al , 1985Griggs and Buddemeier 1986;Holland et al 1987;Holland and Brekke 1988;Brekke et al 1989;Sims et al 1990Sims et al , 1991Gallegos et al 1992Gallegos et al , 1993. The data were analyzed using JMP Version 2, Software for Statistical Visualization on the Apple Macintosh.?…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1970s, the effluent discharge has been subject to continued monitoring before leaving the site. Results of this monitoring can be found in the Lawrence Liver more National Laboratory Annual Monitoring Report (Griggs 1984). Exfiltration through lines are a consideration in assessing ground water contamination sources.…”
Section: J-2 Il General Site Characteristicsmentioning
confidence: 99%
“…The main effluent release from this building is the gaseous release of tritium through the 30 meter high stacks. The stacks are monitored and the amounts released are documented in the LLNL Yearly Monitoring Reports(Griggs 1984).…”
mentioning
confidence: 99%